Tracking Macroprolactin: Use of an Optimized Polyethylene Glycol Precipitation Method More Compatible with the Requirements and Processes of Automated Core Laboratories. (15th October 2019) - Favresse, Julien; Bastin, Pierre; Fillée, Catherine; Luyckx, Francoise; Maiter, Dominique; Gruson, Damien
Abstract: Background: Macroprolactin (MPRL) is a large circulating form of a multimeric prolactin currently thought to be biologically inactive. Because of its ability to interfere with prolactin detection in most of the current 2-site immunoassays, the presence of MPRL can lead to inappropriate diagnosis of hyperprolactinemia and unnecessary investigations and treatments. The main objective of our study was to establish an optimized polyethylene glycol (PEG) precipitation method that could be used in automated core laboratory settings. Methods: The PEG precipitation method adopted in our laboratory (2 min, 19744 g ) was compared to a standard procedure (30 min, 1500 g ). We also tested the stability over time (44, 99, and 261 days) of PEG solutions. Post-PEG prolactin concentrations were used for method comparisons, and discrepancies with the classic recovery calculation were also studied. Results: The higher g -force centrifugation method adopted in our laboratory generated results in agreement with a standard procedure (slope of 1.00, y intercept of −0.8 ng/mL). The PEG solution was stable for at least 261 days ( P = 0.72), and the post-PEG reference values as definition of macroprolactinemia revealed a closer association to clinical presentations than the recovery calculation. Conclusions: We established an optimized PEG precipitation procedure that meets the requirements of core laboratory settings with a more stable PEG solution, less processing samples based on the 30–100 ng/mL screening interval, a lower sample volume, no incubation time, and a higher g -force centrifugation process. Along with post-PEG reference values found in literature, this method could facilitate the widespread introduction of MPRL screening in cases of hyperprolactinemia.